Growth effect of Capsicum annum var. Jwala plants inoculated with Glomus fasciculentum and Trichoderma species - Sarwade, P P; Chandanshive, S S; Kanade, M B; Ambuse, M G; Bhale, U N (International Multidisciplinary Research Journal, 2011)
In the present investigation deals with the beneficial effect of Glomus fasciculentum with Trichoderma harzianum and Trichoderma viride under pot experiment. In dual inoculated Capsicum plant showed significant increase in plant growth parameters like number of leaves, stem diameter, shoot length, number of branching, root length, fresh root weight, dry root weight, fresh shoot weight, dry shoot weight, % of root colonization and number of spores as compared to control. The results reveal that mixed Mycorrhiza and Trichodema species inoculation contribute best growth and development of Capsicum annum plant under pot experiment.Â 